Grower Perceptions of Safety Hazards and Associated Injuries among Farmworkers Involved in Northwest Potato Production. Issue 2 (3rd April 2021) - Curl, Cynthia; Adams, Karin; Phinney, Rachel; Blua, Matthew
ABSTRACT: Background : Potatoes are a vital part of the Pacific Northwest's agricultural economy. As in many agricultural industries, workers involved in potato production may be at risk for illness and injuries. Methods : A Hazard Perception Survey (HPS) was completed by 63 potato growers in Washington (n = 26) and Idaho (n = 37) during the fall and winter of 2017–2018. Participants were asked to indicate their level of concern regarding the frequency and severity of injuries associated with various potato production tasks. Descriptive statistical analyses were used to identify operations and tasks that potato growers perceived to be most hazardous. Results : The majority of growers (70.9%) indicated that they were very concerned about injuries on their farm. Growers reported that tasks requiring bending, twisting, and lifting resulted in the most common and severe injuries, followed by potato sorting during harvest and falling during planting operations. Conclusions : Potato growers were concerned with potential hazards related to a variety of potato production tasks. In response to these concerns, we developed educational materials to assist growers in identifying and mitigating safety hazards on their own establishments. Future research is needed to evaluate the utility of these tools on reducing potential hazards and injury rates among workers in the Northwest potato industry.